LITERASI BUDAYA SEBAGAI KECAKAPAN HIDUP BAGI SISWA DI TINGKAT SEKOLAH DASAR - Nawir, Muhammad; Zakina, Fadila Nur; Ramadhani, Indri; Azizah, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Cultural literacy is an essential life skill that needs to be instilled early on, especially in primary school education. This research aims to examine the urgency of cultural literacy as the foundation of character building and life skills for children in the era of globalization. The method used is a literature study by reviewing various literatures related to the concept, basic principles, and implementation of cultural literacy in education. The results of the study show that cultural literacy not only includes an understanding of cultural values, norms and symbols, but also cross-cultural communication skills, adaptation to differences, and utilization of cultural heritage in everyday life. In the context of basic learning, cultural literacy is proven to broaden students' horizons, strengthen cultural identity and foster tolerant attitudes. The integration of cultural literacy in education can be done through the curriculum, cooperation with local communities, and the use of media and creative activities. This research confirms that cultural literacy plays an important role in shaping individuals who are inclusive, nationalistic and resilient in facing global challenges. Therefore, a systematic and sustainable educational strategy is needed to effectively develop cultural literacy in the primary school environment.